Development of a new synergistic cyber security awareness model for the elderly in Malaysia (SCSAM-elderly) - Alieyah, Nurul; Buja, Alya Geogiana; Masri Sahri, Nor; Ahmad, Rabiah; Abdul Latip, Shekh Faisal; Fadly Habidin, Nurul; Darus, Mohamad Yusof; Shahril Hussin, Mohd; Saat, Saharudin (2023)
This paper proposes a cyber security awareness model for the elderly. Widespread use of the internet has led to the emergence of cybercriminal activities such as scams, fraud schemes, and cyberbullying. It has been reported that the number of cyber security issues is increasing, with the elderly being among the affected demographic. This paper focuses on individuals aged 60 years and above. While several cyber security awareness methods have been used by governments and organisations, many of them are outdated and too complex for elderly individuals, especially those with disabilities or impairments. The objective in this paper is to design, develop, and assess the deployment of a new model using functionality testing. Four methods were used in developing the proposed model, which is called SCSAM-Elderly. The first method involved conducting a feasibility study and literature review. The second step included identifying components with the inputs of experts, with the education component being validated by these experts. The third step comprised the development of the proposed model. The final step entailed functionality testing, which yielded successful results in website development. Therefore, this study aims to propose a new synergistic cyber security awareness model and deploy the website. The findings demonstrate that this model serve as a tool and guide governments or organizations to raise awareness and teach the elderly about cyber security threats.